New pyridinium based ionic dyes for the hydrogen evolution reaction. Issue 1 (4th January 2018) - Konieczna, Dagny D.; Biller, Harry; Witte, Matthias; Schmidt, Wolf Gero; Neuba, Adam; Wilhelm, René
Abstract: The presented work comprised the synthesis and characterization of new ionic organic dyes as potential photosensitizer (PS) in the photocatalytic H2 evolution reaction. The presented dyes are consisting of donor-π-acceptor (D-π-A) structures that are commonly used for organic dyes for organic solar cells. The acceptor is based on a cationic pyridinium moiety. Furthermore, a complex was synthesized, in which a D-π-A photosensitizer is linked as ligand to cobaloxime. The latter is a common proton reduction catalyst. The attached ligand enabled a fast intramolecular electron transfer to the cobalt center. The resulted complex showed high stability and potential in the homogeneous photocatalytic H2 evolution reaction. Finally, one ionic dye showed a high activity when combined with TiO2 and Pt in a heterogeneous hydrogen evolution reactions with a TOF of up to 407 h −1 . Graphical abstract: